GW24-e3765 A Correlational Study about Relationship between ACE Gene Polymorphisms with Heart Failure in Hainan Han Nationality. (1st October 2013) - Lei, Zheng; Zheng Wang, Liu; Ming Jun, Wang; Meiling, Yun
Abstract : Objectives: To study the correlation between angiotensin converting enzyme (ACE)gene polymorphisms with heart failure in Hainan Han Nationality. Methods: ACE I/D gene polymorphisms were detected by polymerase chain reaction (PCR) in 150 cases of heart failure patients and 150 cases of healthy person from Hainan Han nationality, and the genotype frequencies and allele frequencies of DD, DI and II were investigated. Results: There were no significant differences in the frequencies of allele and genotypes between the healthy subjects and patients with heart failure of Han nationality. There were no significant differences between the two groups (P > 0.05). Conclusions: I/D polymorphism of the ACE gene was not related to heart failure in Hainan Han nationality patients, and was not associated with lipid levels in Hainan Han nationality patients with hypertension. Key words ACE gene; Polymorphisms; Heart failure.